What’s new in flow biocatalysis? A snapshot of 2020–2022 - Crotti, Michele; Robescu, Marina S.; Bolivar, Juan M.; Ubiali, Daniela; Wilson, Lorena; Contente, Martina L. (Frontiers in Catalysis, 2023)
Flow biocatalysis is a key enabling technology that is increasingly being applied to a wide array of reactions with the aim of achieving process intensification, better control of biotransformations, and minimization of waste stream. In this mini-review, selected applications of flow biocatalysis to the preparation of food ingredients, APIs and fat- and oil-derived commodity chemicals, covering the period 2020-2022, are described.